2004
DOI: 10.1161/01.cir.0000136581.59584.0e
|View full text |Cite
|
Sign up to set email alerts
|

C-Reactive Protein, the Metabolic Syndrome, and Prediction of Cardiovascular Events in the Framingham Offspring Study

Abstract: Background-Inflammation (assessed by C-reactive protein [CRP]) and the metabolic syndrome (MetS) are associated with cardiovascular disease (CVD), but population-based data are limited. Methods and Results-We assessed the cross-sectional relations of CRP to the MetS (National Cholesterol Education Program Expert Panel on Detection, Evaluation, and Treatment of High Blood Cholesterol in Adults, Adult Treatment Panel III definition) in 3037 subjects (1681 women; mean age, 54 years) and the utility of CRP and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
200
1
7

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 584 publications
(234 citation statements)
references
References 39 publications
26
200
1
7
Order By: Relevance
“…CRP levels and HRs for CHD were similar to those observed in previous publications 3. The prevalence of metabolic risk criteria was in agreement with other large observational cohort studies, whereas the prevalence of the metabolically healthy but obese phenotype was somewhat higher in our population compared with previous studies,19 probably because we defined abdominal obesity by waist circumference, whereas other studies used other measures to determine obesity (eg, body mass index) 12. It must be noted that in view of the subgroups used in our analyses, differences in our population did not always reach our predefined significance level.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…CRP levels and HRs for CHD were similar to those observed in previous publications 3. The prevalence of metabolic risk criteria was in agreement with other large observational cohort studies, whereas the prevalence of the metabolically healthy but obese phenotype was somewhat higher in our population compared with previous studies,19 probably because we defined abdominal obesity by waist circumference, whereas other studies used other measures to determine obesity (eg, body mass index) 12. It must be noted that in view of the subgroups used in our analyses, differences in our population did not always reach our predefined significance level.…”
Section: Discussionsupporting
confidence: 91%
“…Ridker et al previously reported an age‐adjusted HR of 2.3 (95% CI 1.6–3.3) for women with the MS if CRP levels <3 mg/L were present in contrast to the HR of 4.0 (95% CI 3.0–5.4) if CRP levels >3 mg/L were present 9. Rutter et al similarly observed that CRP independently predicted CHD above the presence of the MS in the Framingham prospective cohort study 12. We found similar associations for abdominally obese participants with elevated CRP levels showing an increased risk for CHD compared with abdominally obese participants with low CRP levels.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…132 However, the estimated RR for menstrual irregularity was no greater than 1.5 (95% CI, 1.10-2.04 for overweight, very irregular women), which is comparable to the HRs of 1.65 (95% CI, 1.10-2.47) to 2.1 (95% CI, 1.5-2.8) for cardiovascular events from the metabolic syndrome alone in other cohorts. 133,134 Because menstrual irregularity increases the risk for insulin resistance and DM, 135 risk associated with menstrual irregularity may not be attributable to PCOS per se but to insulin resistance, the metabolic syndrome, or obesity. Other PCOS criteria of androgen excess and polycystic ovaries have been associated with an increased risk for coronary occlusion or cardiovascular events in postmenopausal women.…”
Section: 129mentioning
confidence: 99%
“…The carotid-femoral PWV were analyzed in healthy subjects, hypertensive subjects too and has been shown to be a forecast of future cardiovascular events [45,46]. In studies with patients with acute coronary syndrome and chronic renal disease [47] or heart failure [48], the brachial-ankle PWV has been shown as a predictor of the prognosis for cardiovascular events [49].…”
Section: Assessment Of Arterial Elasticitymentioning
confidence: 99%